TOPOLOGICAL OPERATORS OVER BIPOLAR INTUITIONISTIC FUZZY -IDEAL OF A BP-ALGEBRA (CAHIERS MAGELLANES-NS, 2024)
The idea of an interior operator and a new algebraic structure of BP-algebra is the concept of a bipolar intuitionistic fuzzy α-ideal. This study aims to apply the ideal theory and fuzzy set theory of a BP-algebra. The relationships between the topological operators' operations on the bipolar intuitionistic fuzzy α-ideal are determined.